THE ROLE OF GOVERNMENT POLICY IN SMES FACILITATING INSTITUTIONS IN INDONESIA: A CASE STUDY ON BUSINESS DEVELOPMENT SERVICES PROVIDER - Akhmad, Khabib Alia; Karsidi, Ravik; Rahayu, Endang Siti; Wijaya, Mahendra (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2018)
Small and medium-sized enterprises (SMEs) play an important part in improving the Indonesia economy and, consequently, the government has a mandatory obligation to maintain their sustainability and development. The fact that government has a limitation in helping solve the problems the SMEs encounter, Business Development Service- Provider (BDS-P) can serve as an alternative partner in improving the performances and finding the solution for the problem faced by the SMEs. This research was conducted on BDS-P existing in Indonesia using the qualitative method to describe and to explore in-depth the role of government policy in BDS-P development in Indonesia. The primary data were collected through interviews and observations, while the secondary data were derived from the documentation, notes, and archives. From the data processing and data analysis, it could be concluded that the government policies concerning the development of BDS-P had resulted in the improvement of the ability and capacity of BDS-P in providing business services, dissemination of the BDS-P roles in developing SMEs, involvement of BDS-P in providing business service for SMEs, and the establishment of the standard on the competency certification for professional consultants/ facilitators.